Alzheimer's disease biomarkers: another tool for FAA pilot screening?. Issue 1 (18th July 2019) - Lawrence, Matthew W; Arias, Jalayne J
Abstract: Research advancements to improve the accuracy of diagnosing Alzheimer's disease (AD) have altered clinicians and researchers' understanding of the disease process. The discovery of amyloid and tau biomarkers as measures of disease pathology supports early identification of disease risk that precedes symptom onset. As a result, AD is now understood to be an underlying pathology that causes a spectrum of clinical syndromes, beginning with preclinical AD. Future clinical implementation of biomarkers will raise novel employment and professional licensure discrimination risks based on AD biomarker status. This article evaluates the potential consequences of biomarker status for commercial pilots within Federal Aviation Administration pilot licensing procedures. The article argues for a careful implementation of AD biomarker status in licensing procedures to emphasize public safety, integrate accurate scientific knowledge, and limit unjustified and adverse consequences for individual pilots.